2016
DOI: 10.18632/oncotarget.10562
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-based identification of VDAC1 as a tumor promoter in cervical carcinoma

Abstract: We used oxidative isotope-coded affinity tags (OxICAT) to investigate the global redox status of proteins in human papillomavirus (HPV)-related cervical cancer cells, in order to identify a potential target for gene therapy. Voltage-dependent anion channel 1 (VDAC1) was found to be highly oxidized in HPV-positive cervical cancer cells. VDAC1 expression correlated significantly with the invasion of cervical cancer, the grade of cervical intraepithelial neoplasia (CIN) and the expression of HPV16 E7 in CIN. Knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Cancer is a metabolic disease, and mitochondrial dysfunction is a common feature of cancer (27). A previous study reported that the expression of VDAC1 in tumor tissue, including liver cancer (8), non-small cell lung cancer (9) and cervical cancer (10), was higher compared with that in corresponding normal tissue, and that the protein controlled the fate of cancer cells (20). The results of the present study demonstrated that knockdown of VDAC1 inhibited the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is a metabolic disease, and mitochondrial dysfunction is a common feature of cancer (27). A previous study reported that the expression of VDAC1 in tumor tissue, including liver cancer (8), non-small cell lung cancer (9) and cervical cancer (10), was higher compared with that in corresponding normal tissue, and that the protein controlled the fate of cancer cells (20). The results of the present study demonstrated that knockdown of VDAC1 inhibited the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…non-small cell lung cancer (9). and cervical cancer (10). and that it promotes tumor growth and apoptosis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that cervical carcinoma and precancerous lesions are closely related with HPV infection, HPV-related proteomics is still in its infancy [ 29 ]. The detection rate of high-risk HPV subtypes (such as HPV 16 or 18) in Uygur women with cervical carcinoma is high (78 ~ 88 %), approaching the level of cervical carcinoma in high incidence areas [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because overexpression of VDAC1 triggers cell death, It may be related to the destruction of nerve cells 35 . VDAC1 was identi ed as a tumor promoter in cervical cancer, as well as knock-down of VDAC1 in cervical cancer Cell lines increase the rate at which apoptosis occurs, which was partially reversed by overexpression of VDAC1 36 .…”
Section: Discussionmentioning
confidence: 99%